2017
DOI: 10.1016/j.envres.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Maternal diethylhexyl phthalate exposure affects adiposity and insulin tolerance in offspring in a PCNA-dependent manner

Abstract: The ubiquitous plasticizer, diethylhexyl phthalate (DEHP), is a known endocrine disruptor. However, DEHP exposure effects are not well understood. Changes in industrial and agricultural practices have resulted in increased prevalence of DEHP exposure and has coincided with the heightened occurrence of metabolic syndrome and obesity. DEHP and its metabolites are detected in the umbilical cord blood of newborns; however, the prenatal and perinatal effects of DEHP exposure have not been intensively studied. Previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…We observed transient increases in body weight in females and transient decreases in body weight in males in a few weeks, but taking the entire follow up period into account, no clear impact on body weight was observed. In line with our findings, recent studies report a lack of effects on body weight after developmental exposure to DEHP ( 34 , 36 , 37 ). After 27 weeks of age, we continued with the body weight measurements, performed a locomotion test and studied the glucose homeostasis via glucose and insulin tolerance tests.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We observed transient increases in body weight in females and transient decreases in body weight in males in a few weeks, but taking the entire follow up period into account, no clear impact on body weight was observed. In line with our findings, recent studies report a lack of effects on body weight after developmental exposure to DEHP ( 34 , 36 , 37 ). After 27 weeks of age, we continued with the body weight measurements, performed a locomotion test and studied the glucose homeostasis via glucose and insulin tolerance tests.…”
Section: Discussionsupporting
confidence: 93%
“…The studies above report alteration in serum lipids under a normal diet. In our experimental setting, we studied for the first time the effect of developmental exposure to DEHP in combination with a HFD challenge as calorie-rich diets are tightly linked to the pandemic of metabolic disorders ( 37 ). We pinpoint here increases in 2 parameters out of 4 related to lipid metabolism studied (TG's, FFA, CHOL, HDL-C).…”
Section: Discussionmentioning
confidence: 99%
“…PND 90 females showed no differences in either body weight or body composition. This is consistent with findings from our group and others [26,[33][34][35]. In PND 90 males, on the other hand, HF diet alone as well as 200 μg/kg/day phthalates increased body weight.…”
Section: Perinatal Hf Diet and Phthalate Exposure Alters Body Weight supporting
confidence: 93%
“…In humans, maternal urinary BPA has been associated with increased hip to waist ratios in the offspring, an affect that was more severe in females [109]. Animal studies of BPA and phalate exposure in utero have consistently shown to increase offspring adiposity in later life (Table 5 and [106,[110][111][112]). In part, these changes are associated with enhanced adipocyte size, infiltration of inflammatory leukocytes, and elevated expression of lipogenic markers, like PPAR-γ and SREBP [113].…”
Section: Endocrine Disruptors and Offspring Adipositymentioning
confidence: 99%